Facile controlled synthesis of bifunctional ZnO nanoparticles for application as a high-performance self-powered UV photosensor and highly selective vapor sensor - Kumar Pandey, Rajiv; Choi, Hwayong; Yi, Junsin; Heo, Junseok; Kumar Sahu, Praveen (Materials Science and Engineering: B, 2023)
ZnO has unique multifunctional and morphological properties, and has received significant attention in the field of next-generation sensors and photonic devices. Herein, we report bifunctional ZnO nanoparticles (NPs) used for the selective detection of hazardous gases and self-powered photo response. ZnO nanoparticles with a wurtzite structure and particle size in the range of 10–20 nm were synthesized and fully characterized. ZnO NPs were explored as selective self-powered UV light (370 nm) photosensors and gas sensors. The photoresponse upon illumination with 370-nm light exhibited self-power behavior with an on/off ratio of 1.5x 104, responsivity (R(λ)) of 649 mA/W, external quantum efficiency (EQE) of 217%, and detectivity (D) of 2.4 × 1013 Jones at a bias voltage of 0 V. Maximum sensitivities of 211% and 96% were observed for propanol and chloroform, respectively, among the different gas environments, with quick response, short recovery times, and good repeatability. A possible mechanism has been proposed using the morphology, structural, and electrical characterization results. Thus, our study opens a path for synthesis of multifunctional nanomaterials and their exploration for multiple applications.
Keywords: Bi-functional; Chemiresistors; Gas-sensors; Photosensor; Responsivity; Selectivity; Self-powered; Self-powered photosensor; Sensing mechanism; ZnO nanoparticles; Chemiresistor; Gas sensor; Responsivity; Selectivity; Self-powered photosensors; Sensing mechanism; ZnO nanoparticles